Elements of mathematical model for step in racewalking - Badescu, D. (Science, Movement & Health, 2015)
The aim of the experiment is to realize a simulation based on a mathematical model and to presents a biomechanical model of human body whichever there are studied mechanical work, charts variance on different muscles quarters which training legs and arms, which make more efficient the displacement during the racewalking. Method. Mathematical and biomechanical models were used by applying specific calculation formulas when calcuating the friction energy created in the lower and upper limbs. The data obtained was processed and illustrated in MATCAD. Results. The optimal values of the moving angles of the upper and lower limbs were set, in order to generate the most efficient movement while racewalking, and the energy consumed while making these movements to be minimum. The obtained values were used in the simulation training program in C. D.`s case, and led to an improvement in her technique, her arms movement trajectory and the technique of rolling the foot against the ground were improved. Conclusions. The biomechanical model is able to provide information regarding the proper rotation angles in order to reduce the muscular effort, as well as to perform correct movements technically speaking.